2002
DOI: 10.1046/j.1432-1033.2002.02837.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for poor uracil excision from hairpin DNA

Abstract: Two-dimensional NMR and molecular dynamics simulations have been used to determine the three-dimensional structures of two hairpin DNA structures: d-CTAGAG GATCCUTTTGGATCCT (abbreviated as U1-hairpin) and d-CTAGAGGATCCTTUTGGATCCT (abbreviated as U3-hairpin). The 1 H resonances of both of these hairpin structures have been assigned almost completely. NMR restrained molecular dynamics and energy minimization procedures have been used to describe the three-dimensional structures of these hairpins. This study and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…We therefore conclude that the large differences in the rates of base opening are due to differences in the protein–nucleic acid interface. This is supported by previous studies that have observed large K M effects when the target uracil is placed within the unusual DNA structure of a hairpin (40,41). The logical conclusion therefore is that protein–DNA interactions are critical in uracil eversion that requires active engagement of the UNG enzyme with the DNA.…”
Section: Resultssupporting
confidence: 82%
“…We therefore conclude that the large differences in the rates of base opening are due to differences in the protein–nucleic acid interface. This is supported by previous studies that have observed large K M effects when the target uracil is placed within the unusual DNA structure of a hairpin (40,41). The logical conclusion therefore is that protein–DNA interactions are critical in uracil eversion that requires active engagement of the UNG enzyme with the DNA.…”
Section: Resultssupporting
confidence: 82%
“…Cytosine deamination in DNA to uracil occurs 100−500 times per human cell per day, generating G:U mismatches, which become transition mutations to A:T if the damaged DNA is replicated . Misincorporation of dUTP can also occur, generating A:U mismatches during DNA replication. , Apart from TS analysis of eUDG, the catalytic mechanisms of eUDG, hUDG, and hsvUDG have been elucidated in detail by NMR, ,, X-ray crystallography, ,,,, Raman spectroscopy, mutational analysis, ,,,,, inhibitor studies, ,,, and computation. , These studies have addressed how UDG searches DNA for uracil residues, the conformational changes involved in flipping the target residue into the active site, plus studies of the chemical steps. Many of the mechanistic findings have been reviewed in detail , and are outlined briefly below.…”
Section: 1 Uracil Dna Glycosylasementioning
confidence: 99%
“…To understand the modulation of UDG activity by local DNA conformation, a series of NMR studies have determined the structure of dU-containing hairpins (Chart ), observing similar stem structures but with marked conformational differences at the loop region. The RMD structure of the U4 hairpin ( 52d ) (PDB code 1QE7) shows the uracil base stacked between the 3‘- and 5‘-flanking residues and B I -DNA values for the sugar−phosphate backbone angles at the loop region . Conversely, in the refined structure of the U2 ( 52b ) hairpin (PDB code 1DGO) where UDG uracil incision is retarded the most, dU and its 3‘-flanking residue adopt syn conformations around the glycosidic torsion angle and the α, γ, and ζ backbone dihedral angles of the loop assume the unusual trans conformation .…”
Section: Nucleotide Deamination Damagementioning
confidence: 99%
“…Conversely, in the refined structure of the U2 ( 52b ) hairpin (PDB code 1DGO) where UDG uracil incision is retarded the most, dU and its 3‘-flanking residue adopt syn conformations around the glycosidic torsion angle and the α, γ, and ζ backbone dihedral angles of the loop assume the unusual trans conformation . RMD structures of the U1 ( 52a ) and U3 ( 52c ) (PDB codes 1II1 and 1IDX, respectively), that are incised by UDG somewhat more efficiently than the U2 hairpin, show all loop residues in anti coformations and a trans conformation for backbone dihedral angles of the dU residue . On the basis of these observations and of X-ray data available for E. coli UDG, the authors proposed that a stretched out backbone conformation of the dU nucleotide reduces the affinity of the scissile residue for UDG.…”
Section: Nucleotide Deamination Damagementioning
confidence: 99%